2009
DOI: 10.1371/journal.pone.0007996
|View full text |Cite
|
Sign up to set email alerts
|

Differential Axial Requirements for Lunatic Fringe and Hes7 Transcription during Mouse Somitogenesis

Abstract: Vertebrate segmentation is regulated by the “segmentation clock”, which drives cyclic expression of several genes in the caudal presomitic mesoderm (PSM). One such gene is Lunatic fringe (Lfng), which encodes a modifier of Notch signalling, and which is also expressed in a stripe at the cranial end of the PSM, adjacent to the newly forming somite border. We have investigated the functional requirements for these modes of Lfng expression during somitogenesis by generating mice in which Lfng is expressed in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
39
2

Year Published

2010
2010
2016
2016

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 32 publications
(42 citation statements)
references
References 72 publications
1
39
2
Order By: Relevance
“…The authors of these reports produced transgenic mice harboring Lfng expression without oscillation. Their data indicate that cNICD oscillation is disrupted, but that normal segmented somites form, after E10.5 and they concluded that oscillating Lfng expression is required only for early stage, but not later stage, somitogenesis (Shifley et al, 2008;Stauber et al, 2009). We wish therefore to discuss some possible explanations for the discrepancies between our current findings and these previous experimental results.…”
Section: Functions Of Lfng In the Posterior And Anterior Psm During Mcontrasting
confidence: 66%
See 4 more Smart Citations
“…The authors of these reports produced transgenic mice harboring Lfng expression without oscillation. Their data indicate that cNICD oscillation is disrupted, but that normal segmented somites form, after E10.5 and they concluded that oscillating Lfng expression is required only for early stage, but not later stage, somitogenesis (Shifley et al, 2008;Stauber et al, 2009). We wish therefore to discuss some possible explanations for the discrepancies between our current findings and these previous experimental results.…”
Section: Functions Of Lfng In the Posterior And Anterior Psm During Mcontrasting
confidence: 66%
“…It is reasonable to assume that the requirement of Notch clock oscillation by Lfng changes during somitogenesis and is lesser at later stages, as now suggested by a number of studies (Shifley et al, 2008;Stauber et al, 2009). …”
Section: Research Articlementioning
confidence: 91%
See 3 more Smart Citations